Monocyte Lymphocyte Ratio as a Possible Prognostic Marker in Antituberculous Therapy - Sumaira Iqbal, Umbreen Ahmed, Syed Badshah Hussain Zaidi (Journal of Rawalpindi Medical College, 2014)
Background :To assess monocyte lymphocyte ratio (M/L ratio) as a biomarker to see the outcome of therapy and progress of tuberculosis. Methods: In this descriptive study 45 newly diagnosed cases of tuberculosis and 45 age and sex matched healthy controls, were enrolled. The study was designed to determine the baseline, initiation phase and 2-months maintenance phase treatment values of M/L ratio in newly diagnosed active TB cases. Blood complete counts were performed in automated haematology analyzer. Manual differential leukocyte count was done by microscopy to determine M/L ratio. Results: The pre-treatment lymphocyte and monocyte count in the study group were significantly different from the control group, while M/L ratio was similar in both the groups. The mean M/L ratio in cases and controls were 0.24 ± 0.14 and 0.24 ± 0.07 respectively. The M/L ratio significantly decreased after initiation phase and two months of maintenance phase of treatment from baseline 0.24 ± 0.14 to 0.20 ± 0.10 to 0.19 ± 0.10 with p value of 0.006. Conclusions: Tuberculosis is associated with increased M/L ratio, which declines and returns to normal with antituberculous therapy.